A thing of the past? Household surveys in a rapidly evolving (agricultural) data landscape: Insights from the LSMS‐ISA. (18th November 2019) - Carletto, Calogero; Gourlay, Sydney
Abstract: Household surveys, a pivotal component of every country's national statistical system, continue to be criticized and praised in equal manner. While recognizing their limitations, it is clear that certain types of data must continue to be collected through household surveys, preferably in an integrated manner with other data sources. This is particularly true in the agricultural space for which household and farm surveys will be critical both to collect primary data as well as to validate alternative data sources. Recent methodological gains and technological innovations offer a unique opportunity to address many of the shortcomings of agricultural data. In this article, we briefly describe select examples of such methodological and technological changes, drawing from the Living Standards Measurement Study‐Integrated Surveys on Agriculture, a survey program aimed at improving the availability, quality, and relevance of agricultural data in multitopic, multipurpose household surveys.